PELANGGARAN BHISAMA KESUCIAN PURA DI SEKITAR PURA DANG KAHYANGAN DI KECAMATAN KUTA SELATAN, KABUPATEN BADUNG - Sutrisna W P, A A Gde (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment); Vol 3 No 3 (2016): Oktober 2016, 2016)
Bali partially owes its reputation to the existence of the thousand temples it has scattered across its territory. Its unique culture evolves around the ritual and symbolic significances that each temple is believed to possess. The area surrounding each temple is recognized as a sacred zone whose scale varies from one temple to another depending on its importance. Bali's Provincial Regulation Number 16, year 2009 has clearly delineated this zone as an undeveloped area; a protected territory and to be measured in relation to a specific region, measured by taking a specific radius and circumference using the temple as the central pivot. This study evaluates how this regulation has been violated, especially in the case of Dang Kahyangan temples located in a touristy area of South Kuta District. The protected zone of both temples stretches in theory, to a radius of 2 km. In practice, things are radically different. The research suggests that violations have taken place in various forms. The breaches are a consequence of many conditions including the lack of initiative to implement then police the regulation; the absence or elasticity of control over development; and public discontent due to the lack of compensation for development rights. Any such regulation without state compensation is unjust. This article also investigates the impacts such violations have, both negatively and positively. The article concludes with some recommendations as to how a balance can be achieved between such competing interests. Keywords: conserved zone; sacred zone; Dang Kahyangan temple; bhisama ; land development Abstrak Bali memiliki kewajiban mempertahankan keberadaan kesucian ratusan pura yang tersebar di seluruh wilayahnya. Keunikan budayanya meliputi prosesi ritual dan makna simbolik yang dipercaya dimiliki oleh masing-masing pura tersebut. Kawasan sekitar pura dikenal sebagai kawasan suci yang memiliki variasi radius kesucian bergantung pada kepentingannya. Peraturan Daerah Provinsi Bali No. 16 tahun 2009 tentang Rencana Tata Ruang Wilayah Provinsi Bali telah mengatur perlindungan pada kawasan suci yang tidak boleh dibangun yaitu pada radius tertentu dengan pura sebagai titik pusatnya. Studi ini mengevaluasi bagaimana peraturan ini telah dilanggar, khususnya di kawasan sekitar pura Pura Dang Kahyangan di Kecamatan Kuta Selatan pada radius 2 km. Hasil penelitian menunjukkan bahwa terjadi pelanggaran terhadap Bhisama kesucian pura dalam bentuk kegiatan. Pelanggaran ini disebabkan adanya kebijakan pengembangan kawasan pariwisata di kawasan dengan radius kesucian pura dan kurangnya sosialisasi akan pentingnya radius kesucian pura dan tuntutan kebutuhan ekonomi. Studi ini juga menginvestigasi dampak positif maupun negatif dari berbagai macam pelanggaran tersebut. Simpulan dari studi ini adalah beberapa rekomendasi untuk menyeimbangkan antara hasil yang telah dicapai dengan berbagai hal yang relevan.
Keywords: kawasan konservasi; daerah sakral; Pura Dang Kahyangan; bhisama; pengembangan lahan